2021
DOI: 10.3389/fimmu.2021.778298
|View full text |Cite
|
Sign up to set email alerts
|

Dual UMIs and Dual Barcodes With Minimal PCR Amplification Removes Artifacts and Acquires Accurate Antibody Repertoire

Abstract: Antibody repertoire sequencing (Rep-seq) has been widely used to reveal repertoire dynamics and to interrogate antibodies of interest at single nucleotide-level resolution. However, polymerase chain reaction (PCR) amplification introduces extensive artifacts including chimeras and nucleotide errors, leading to false discovery of antibodies and incorrect assessment of somatic hypermutations (SHMs) which subsequently mislead downstream investigations. Here, a novel approach named DUMPArts, which improves the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The two main sources of errors in typical HTS-based approaches are sample preparation (reverse transcription and PCR) and errors inherent to the DNA sequencing platform 10,44 . Our DUMPArts method eliminates the intrinsic artifacts in AIRR pro ling 13 . In this study, we further modi ed the protocol, attaching the Illumina sequencing adapter to the amplicons during the PCR process to enable direct sequencing -LibFree DUMPArts (Fig.…”
Section: Libfree Dumparts Yielded High-quality Ultra-deep Pan-tissue ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The two main sources of errors in typical HTS-based approaches are sample preparation (reverse transcription and PCR) and errors inherent to the DNA sequencing platform 10,44 . Our DUMPArts method eliminates the intrinsic artifacts in AIRR pro ling 13 . In this study, we further modi ed the protocol, attaching the Illumina sequencing adapter to the amplicons during the PCR process to enable direct sequencing -LibFree DUMPArts (Fig.…”
Section: Libfree Dumparts Yielded High-quality Ultra-deep Pan-tissue ...mentioning
confidence: 99%
“…1D). We previously showed that using dual UMIs can e ciently remove the intra-sample chimeras in IgM repertoires 13 . Here, we checked the antibody groups generated by single and dual UMI.…”
Section: Libfree Dumparts Yielded High-quality Ultra-deep Pan-tissue ...mentioning
confidence: 99%
See 3 more Smart Citations